Study of Renal Profile in Babies with Perinatal Asphyxia in a Tertiary Care Hospital: A Prospective Case Control Study - Roy, Banasree; Mondal, Gobinda (Journal of Nepal Paediatric Society, 2013)
Introduction: Perinatal asphyxia is one of the important causes of preventable cerebral injury occurring in the neonatal period. Kidney is one of the most commonly affected organs leading to renal functional abnormality and blood electrolyte imbalance. This was a prospective case control study done in the NICU and neonatal unit at a tertiary care hospital. The objective of this study were to detect renal functional abnormality and electrolyte imbalance (sodium and potassium) among babies with perinatal asphyxia and to correlate severity and type of renal involvement with degree of asphyxia. Materials and Methods: Thirty two neonates for perinatal asphyxia and 32 babies selected randomly from non asphyxiated babies for the control group. Blood samples were taken for measurement of serum urea, creatinine, sodium and potassium levels on 1st and 3rd day of life. If any abnormality detected, values were repeated every alternate days till it become normal. Results: There were total 32 cases (asphyxiated). Among 32 cases 14 (43.75 %) had elevated levels of urea and creatinine on day 1 [Mean urea (43.21± 23.08), creatinine (1.14 ± 0.57)], 18 (56.25%) had elevated levels of urea and creatinine on day 3.Mean urea (58.06 ± 28.52) and creatinine (1.24±0.5) were significantly higher on day 3 (p value<0.05) in study group as compared to control. Mean urea and creatinine levels showed increasing trend with degree of severity of hypoxic ischaemic encephalopathy. Eighteen babies with perinatal asphyxia developed renal failure (56.25%). 18 had Hyponatremia on day 1 (56.25%), 3 of them had value < 125 meq /l. Conclusion: Among study cases significantly higher values of urea and creatinine were found than controls. The values were positively correlated to the degree of asphyxia. Though, mean sodium and potassium level was within the normal limit, the value of potassium was higher among cases than controls. DOI: http://dx.doi.org/10.3126/jnps.v33i3.8385 J. Nepal Paediatr. Soc. 2013;33(3):206-212